Problems of the History and Modern Situation of the Tuva-Mongol Relations - Dongak, Venera S. (The New Research of Tuva, 2010)
The paper is dedicated to problems of the history and modern situation of Tuva-Mongol relations. The intensity of these relations depended on the constantly changing geopolitical, economic, and ethnosocial conditions. Mongol influence had a great affect on the ethnocultural history of Tuva from the thirteenth century till the middle of the twentieth century.
Keywords: Chengis-Khan expansion; protectorate; Tuva People's Republic; Sayan-Altaj Upland; international situation; Mongol lingual tribes; indigenous population; problem of state frontier; controversial area